Effectiveness of a parenting programme to reduce violence in a cash transfer system in the Philippines: RCT with follow-up - Lachman, JM; Alampay, LP; Jocson, RM; Alinea, C; Madrid, B; Ward, C; Hutchings, J; Mamauag, BL; Garilao, MAVFV; Gardner, F (Elsevier, 2021)
Background Parenting interventions and conditional cash transfer (CCT) programmes are promising strategies to reduce the risk of violence against children, but evidence of the effectiveness of combining such programmes is lacking for families in low- and middle-income countries with children over two years of age. This study examined the effectiveness of a locally adapted parenting programme delivered as part of a government CCT system to low-income families with children aged two to six years in Metro Manila, Philippines. Methods Participants were randomly assigned (1:1) to either a 12-session group-based parenting programme or treatment-as-usual services (N = 120). Participation in either service was required among the conditions for receiving cash grants. Baseline assessments were conducted in July 2017 with one-month post-intervention assessments in January-February 2018 and 12-month follow-up in January-February 2019. All assessments were parent-report (ClinicalTrials.gov: NCT03205449). Findings One-month post-intervention assessments indicated moderate intervention effects for primary outcomes of reduced overall child maltreatment (d = -0.50 [-0.86, -0.13]), emotional abuse (d = -0.59 [-0.95; -0.22]), physical abuse (IRR = 0.51 [0.27; 0.74]), and neglect (IRR = 0.52 [0.18; 0.85]). There were also significant effects for reduced dysfunctional parenting, child behaviour problems, and intimate partner violence, and increased parental efficacy and positive parenting. Reduced overall maltreatment, emotional abuse, and neglect effects were sustained at one-year follow-up. Interpretation Findings suggest that a culturally adapted parenting intervention delivered as part of a CCT programme may be effective in sustaining reductions in violence against children in low- and middle-income countries.